2014
DOI: 10.5267/j.esm.2014.4.006
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of HA/AL2O3 nanoparticles on mechanical properties of restoration materials

Abstract: Nano composite materials based on polymers are widely used in restoration martials like dental. Poly methyl methacrylate (PMMA) is one of the most used polymers as dental material. PMMA has disadvantages such as low flexural strength properties and impact strength. In this paper, the influences of additive aluminum oxide and hydroxyapatite nanoparticles on the mechanical and strength properties of PMMA (including flexural strength, impact strength, surface hardness and shrinkage behavior) is studied experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 27 publications
(41 reference statements)
4
34
0
Order By: Relevance
“…96 Dental composites reinforced with nanoparticles displayed high hardness values. 60 Balos et al found that using SiO 2 with agglomerate size of 50 nm at very low loading (0.023 wt%) increased the hardness of PMMA denture base composites. 103 Incorporating ZrO 2 particles with average sizes of 5-15 nm in PMMA denture base at different loadings (1.5, 3, 5 and 7 wt%) significantly increased hardness at 7 wt%.…”
Section: The Effect Of Particle Size On Hardnessmentioning
confidence: 99%
See 2 more Smart Citations
“…96 Dental composites reinforced with nanoparticles displayed high hardness values. 60 Balos et al found that using SiO 2 with agglomerate size of 50 nm at very low loading (0.023 wt%) increased the hardness of PMMA denture base composites. 103 Incorporating ZrO 2 particles with average sizes of 5-15 nm in PMMA denture base at different loadings (1.5, 3, 5 and 7 wt%) significantly increased hardness at 7 wt%.…”
Section: The Effect Of Particle Size On Hardnessmentioning
confidence: 99%
“…The hybrid nano-composites with 5 wt% and 10 wt% of HA and 6 wt% of Al 2 O 3 had the maximum flexural strength. 60 Two similar studies evaluated the effects of incorporating silver (Ag) particles (38 nm) into PMMA denture base. 61,62 Ag filler was incorporated at very low loadings (0.5 wt%) and (0.05 wt% and 0.2 wt%).…”
Section: 54mentioning
confidence: 99%
See 1 more Smart Citation
“…116 In addition to improving surface roughness, 109 tensile strength, flexural modulus, 114 hardness, and thermal conductivity, 116 and radiopacity 111 as well as reducing shrinkage, 107,110 it has antibacterial properties without showing cytotoxicity. 108 A combination of fibers and other fillers also increased impact strength, hardness, 112 surface roughness, and thermal conductivity, 113 as well as compressive and fatigue strengths.…”
Section: Hybrid Reinforcementmentioning
confidence: 99%
“…106 As listed in Table 3, the combination may be between different fibers, 7 different metal oxides and ceramics, [107][108][109][110][111] and fibers with metal oxides, 112,113 or ceramic materials. 48,[114][115][116] Hybrid fiber reinforcement significantly increased the flexural strength and toughness of reinforced acrylic resin.…”
Section: Hybrid Reinforcementmentioning
confidence: 99%